SAT0300 High proportions of dementia among sle patients: a big data analysis. (15th June 2017) - Gendelman, O; Tiosano, S; Comaneshter, D; Cohen, A; Shoenfeld, Y; Amital, H
Abstract : Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease affecting wide range of systems including the peripheral and central nervous system 1 . Cognitive impairment leading to dementia is one of the harmful central nervous system manifestations of SLE 2 . Objectives: The aim of this study was to investigate the association of SLE and dementia. Methods: A cross-sectional study was performed utilizing Clalit Health Care database, the largest HMO in Israel with more than 4.4 million enrollees. SLE patients were compared in a 1:5 ratio to age and sex matched controls. Chi-square and t tests were used for univariate analysis, and a logistic regression model was used for multivariate analysis. Results: The study included 4886 SLE patients and 24, 430 age and sex frequency matched controls without SLE. The proportion of dementia was higher among SLE patients compared to controls (1.56% and 0.51% respectively; p<0.001). This finding was consistent across all age groups by univariate analysis. In a multivariate logistic regression analysis, SLE was significantly associated with dementia (OR =2.039, 95% CI =1.110–2.039). Conclusions: SLE is significantly associated with dementia. This finding should give rise to search for SLE in patients with an ambiguous cause for dementia, especially those with an early onset cognitive decline. References: Tsokos GC. Systemic Lupus Erythematosus. N Engl J Med. 2011;365(22):2110–2121. Liang MH, Corzillius M, Bae SC, et al. The American College of Rheumatology nomenclature and case definitions for neuropsychiatric lupus syndromes. Arthritis Rheum. 1999;42(4):599–608. Disclosure of Interest: None declared